A customised safety assurance assessment model for a liquefied natural gas tanker [electronic resource] - Manivannan Subramaniam, 1969- (2012)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2012